Formação e trabalho dos coordenadores pedagógicos nas escolas municipais de Francisco Beltrão-Paraná - Manarin, Camila (2020)
This thesis is bound to the line of research Culture, Educational Processes, and Teacher Training of the Graduation Program in Education of Francisco Beltrao (PPGEFB), master’s degree, at the Western Paraná State University (UNIOESTE), whose discussions concerns the investigations of the interrelationship between culture and education, teacher training, and formal and non-formal educational processes, in their theoretical-practical, sociopolitical, and pedagogical dimensions. It comes from the discussions of the research group Higher Education, Training, and Teaching Work (GESFORT), linked to the same graduation program, aiming to analyze policies directed to the training and teaching work in different levels and forms of teaching. Thus, the thesis’s topic relates to the teacher training with discussions on training and the work of pedagogical coordinators and their particularities at constituting their own professionality. The main objective is to analyze how these pedagogical coordinators see the need for a specific knowledge for the work in the pedagogical sector at their schools in Francisco Beltrao, a city in the state of Parana. The methodology is based on Filho & Gamboa (2013), as a critical-dialectical approach, which allows us to analyze the data collected in their entirety. It uses a bibliographic and documental methodology based on the functions of the Pedagogical Coordinator, and their developments. It also collects data via questionnaires and semi-structured interviews answered by the pedagogical coordinators working at the elementary schools of Francisco Beltrao. This research relies on discussions as present in Contreras (2012) and Charlot (2013), which discuss the teaching professionality related to the leadership of teachers, as well as the relationships between education and politics, crucial aspects for this dissertation. For the discussion of issues related to the work of the pedagogical coordinators and their developments, our primary sources are ANFOPE’s documents. These show us a theoretical struggle over the function of that worker, as well as authors grounding the pedagogical work in schools, such as Franco (2008a, 2008b) and Libaneo (2008, 2010). Finally, Azzi (2012) and Houssaye (2004) are used as a basis for the distinction between popular knowledge and academic knowledge, a central aspect of our debate. In the data analysis conducted, some categories have emerged. They are thought of as dimensions of the work developed by the pedagogical coordinators involved in the study, with emphasis on teacher planning, emotional, and bureaucracy dimensions. These dimensions are relevant for showing us the reality of the work at the school’s pedagogical departments towards the training of the person working at it, evidencing the transformations of a fragmented professional profile into a polyvalent one, away from the unitary pedagogical worker aimed. Furthermore, the present dissertation shows that the pedagogical coordinators interviewed sense the need for specific knowledge and a theoretical deepening, which are essential to the tasks they conduct. They make explicit this theoretical emptiness in the initial training, but they do not understand the dimension of this pedagogical knowledge, reducing their activities to experiential knowledge.